Conservation of isolated Atlantic heathlands in the Mediterranean region: effects of land-use changes in the Montseny biosphere reserve (Spain) - Bartolomé, Jordi; Plaixats, Josefina; Fanlo, Rosario; Boada, Martí (Biological Conservation, 2005)
In the Mediterranean region, cycles of controlled burning combined with continuous grazing appear to have been an effective tool for maintaining isolated Calluna vulgaris heathlands in the form in which they occur in many places in the Atlantic region. Changes in land use and management of the mosaic of extensively exploited heathland and associated grassland over recent decades, such as bringing land into cultivation followed by its abandonment and the prohibition of fires has resulted in a process of transformation into new shrub communities with lower biodiversity. In the Mediterranean region, these changes are similar to those described in the Atlantic area, but encroachment occurs faster and could lead ultimately to afforestation by Mediterranean woodland.
Keywords: calluna vulgaris; fire; grassland; Grazing; landscape